Pengaruh Literasi Akuntansi dan Academic Self Efficacy terhadap Academic Fraud di Kalangan Mahasiswa - Mutiara Santika, Desta; Nusantoro, Jawoto; Febri Darmayanti, Elmira (Universitas Muhammadiyah Metro, 2025)
This research was conducted with the aim of to see whether or not there is an effect of accounting literacy and academic self-efficacy on academic fraud among undergraduate students. Accounting University of Muhammadiyah Metro. Researchers use the quantitative method as the type of research. In this study using primary data obtained through questionnaires. data obtained through questionnaires. The population used in this study amounted to 279 students then the sampling technique for this study was minimized using the formula slovin formula and get a total sample size of 165 respondents. All data on This research was processed using the help of the IBM SPSS 26 program. The results of the research that has been conducted show that Accounting Literacy has an effect on Academic Fraud. on Academic Fraud, Academic Self Efficacy affects Academic Fraud, and Academic Self Efficacy affects Academic Fraud. on Academic Fraud, and Accounting Literacy and Academic Self Efficacy together affect Academic Fraud Among Undergraduate Accounting Students at the University of Muhammadiyah Metro. Muhammadiyah Metro